Express method for determining the probability of developing congenital pneumonia in preterm infants with low body weight - A.N. Harachka; A.V. Sukalo (Zaslavsky O.Yu., 2021)
Background. According to the World Health Organization, more than 2 million children under the age of five die from pneumonia every year, accounting for almost 1 in 5 deaths. Therefore, the aim of the study was to develop a mathematical model for determining the probability of developing congenital pneumonia in premature infants with low body weight by the express method. Materials and methods. A comprehensive examination of 171 newborns who stayed at the maternity physiology department, the department of anesthesiology and resuscitation (with wards for newborns) and the pediatric department for premature newborns of the State Institution "Republican Scientific and Practical Center "Mother and Child" was conducted. Results. A comparative analysis was carried out of more than 200 life history data, outcomes of previous pregnancies, complications of present pregnancy and clinical and laboratory methods of research in newborns in the first three days of life. Subsequently, the most significant factors associated with the development of congenital pneumonia in premature infants with low body weight were determined. The mathematical analysis of more than 380 million connections of variables is carried out. As a result of the survey, compared with the comparison group and the control group, the most significant factors were established: from the obstetric-gynecological and somatic history of the mother's life - non-developing pregnancy (odds ratio (OR) = 13.46 (10.11-17.91); OR = 32.72 (24.76-43.22)) and spontaneous miscarriage (OR = 3.79 (2.69-5.35); OR = 19.19 (14.57-25.26)); from the complications of a present pregnancy - chronic fetoplacental insufficiency (OR = 3.47 (2.48-4.87); OR = 38.29 (28.78-50.91)), intrauterine growth restriction syndrome (OR = 11.56 (8.70-15.35)) and the threatened miscarriage (OR = 2.73 (1.76-4.23); OR = 3.96 (2.51-6.25)); according to the results of clinical manifestations in infant in the first three days of life - severe respiratory failure (OR = 6.90 (5.01-9.49)). Based on the obtained data, a mathematical model was developed with a sensitivity of 76.4 %, specificity - 83.0 %, and the area under the ROC curve = 0.840 ± 0.056 (0.76-0.91), p < 0.001. Conclusions. Using the model, threshold values were calculated: for non-developing pregnancy - 0.769, spontaneous miscarriage - 0.493, chronic fetoplacental insufficiency - 0.366, intrauterine growth restriction syndrome - 0.334, threatened miscarriage - 0.283, respiratory failure degree III - 0.703, which at the threshold values ≥ 0.49 allows us to single out a high-risk group for the development of congenital pneumonia among premature infants with low body weight.